Attitudes of Elementary School Teachers Towards Inclusive Education: Implementation of the SACIE-R Scale - Musayaroh, Siti; Maryanti, Rina; Ashri Maulidina, Citra (Jurnal Basicedu, 2023)
Children with special education needs (SEN) studying in inclusive classes are still a hot issue to be discussed. This study aims to investigate the attitudes of elementary school teachers towards inclusive education in Indonesia. A total of 64 elementary school teachers participated in filling out SACIE-R questionnaire. The questionnaire consists of three subscales, namely sentiment, concern, and attitude. The data were analyzed using non-parametric statistics (Spearman Correlation coefficient) and multiple regression analysis. The results show that the attitude of elementary school teachers towards inclusive education is positive with a mean SACIE-R (M = 3.00). Elementary school teachers have fears that they do not have knowledge and skills required to teach students with SEN and are not ready to teach students who require communicative technology (e.g. Braille and sign language) in their classrooms. The duration of teaching experience, teaching, and training experience with children with SEN positively correlated to the concern subscale. Special skill training such as Braille and sign language for elementary school teachers is needed to help them overcome their worries and unpreparedness to teach children with SEN in inclusive classes.